Transfer Informasi Intra Industri atas Pengumuman Laba Perusahaan di Bursa Efek Jakarta - Umi Murtini; Bilty Anthoni Parinsi (Fakultas Bisnis UKDW, 2008)
This research examines the existence of inter-induxry information on earning announcement especially for companies within specific sector. The sample is derived from companies which announce their earning on 2003 until 2005. Further, the sample is divided into two groups, namely, control sample and treatment sample. The result shows that earning announcement wkich contains good news will be positively responded by the investor. On the contrary, the bad news on earning announcement will be negatively responded. Baised on the result, it can conclude that inter-industry information exist on earning announcement.Keywords: Inter-industry, earning announcement, good news, bad news